2022
DOI: 10.1021/jacs.1c11457
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Catalytic Supramolecular Assemblies of Melamine- and Imidazole-Based Dynamic Building Blocks

Abstract: The development of synthetic nonequilibrium systems has gathered increasing attention due to their potential to illustrate the dynamic, complex, and emergent traits of biological systems. Simple building blocks capable of interacting via dynamic covalent chemistry and physical assembly in a reaction network under nonequilibrium conditions can contribute to our understanding of complex systems of life and its origin. Herein, we have demonstrated the nonequilibrium generation of catalytic supramolecular assembli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Interestingly, at 1:2 molar ratio, the mixture of Im - K (4 mM) and AS (8 mM) rapidly became viscous and eventually resulted in a self-supported gel after ca. 10 min (Figures a,b, imine formation was confirmed by reductive amination and mass spectrometry, see section S2.3.11 in SI for details) . The gel remained stable for ca.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, at 1:2 molar ratio, the mixture of Im - K (4 mM) and AS (8 mM) rapidly became viscous and eventually resulted in a self-supported gel after ca. 10 min (Figures a,b, imine formation was confirmed by reductive amination and mass spectrometry, see section S2.3.11 in SI for details) . The gel remained stable for ca.…”
mentioning
confidence: 80%
“…Previously, we had shown that equilibrated short peptide-based assemblies can use imine bond for improved catalysis . Such dynamic covalent bond formation utilizing the primary amine of lysine has been widely exploited by natural enzymes and proteins, from the beautiful phenomena of visual phototransduction to the covalent catalysis seen in biosynthetic shikimate pathway and so forth. , An amyloid sequence 16 KLVFFAE derived from the nucleating core of Aβ (1–42) featuring a lysine residue at 16th position was condensed with imidazole acetic acid, leading to the sequence Im - K LVFFAE-NH 2 ( Im - K , Figure ). The negatively charged activated ester (2-(4-formylphenoxy)-2-oxoethanesulfonate, AS ; A stands for aldehyde group) featured a −CHO moiety to reversibly bind to the peptides via formation of an imine bond with the lysine ( 16 K ).…”
mentioning
confidence: 99%
“…The chemically fueled transient volume phase transition (TVPT) of poly(methacrylic acid) microgels has been reported by the introduction of the CRN comprising carboxylic anhydride formation and water‐induced hydrolysis [40] . These chemical systems have also afforded chemically fueled transient payload release [40–43] and/or catalytic activity [44] . However, a polymer hydrogel that exhibits the transient structural change fueled by a biomacromolecule has not been reported.…”
Section: Figurementioning
confidence: 99%
“…Besides thermodynamics concerns, kinetic control of assembly pathways, intermediates, and the lifetime of assemblies are also important issues. In recent years, progress has been made by coupling chemical reactions with molecular assembly approaches, namely, chemical-fueled non-equilibrium self-assembly, , to construct temporally controlled transient supramolecular assemblies. Pioneering works , from van Esch et al reported a chemical-fueled supramolecular polymerization that was controlled in situ by reversible esterification and hydrolysis that was used to produce transient supramolecular hydrogels.…”
Section: Introductionmentioning
confidence: 99%